Tissue-type plasminogen activator increases the binding of glu-plasminogen to clots. - Tran-Thang, C (1984)
Porcine tissue-type plasminogen activator (t-PA) increases the binding of 125I-glu-plasminogen to clots made from human plasma or purified fibrinogen in a time and t-PA concentration dependent fashion. The accumulation of plasminogen was faster and greater on noncrosslinked plasma clots than on clots which had been crosslinked by Factor XIIIa. Furthermore, the uptake of plasminogen to crosslinked fibrin clots occurred at a slower rate in the presence of alpha 2-plasmin inhibitor (alpha 2 PI) than in its absence. The kinetics of the uptake of 125I-plasminogen were analyzed using SDS-polyacrylamide gel electrophoresis and radioautography of solubilized plasma clots formed in the presence of t-PA. During the initial phase there was a decrease of clot-bound glu-plasminogen; simultaneously, there was a slight increase in clot-bound glu-plasmin and in plasmin complexed to alpha 2 PI that was crosslinked to alpha-chain polymers of fibrin. This was followed by a marked increase in clot-bound plasminogen having glutamic acid as NH2-terminal (glu-plasminogen) and gluplasmin. t-PA-induced enhancement of glu-plasminogen uptake appears to be mediated by plasmin but does not require the conversion of glu-plasminogen to plasminogen having lysine or methionine as NH2-terminal. The described mechanism assures an adequate supply of clot-bound plasmin, which is the enzyme ultimately involved in the degradation of fibrin.